Criminal Property Forfeiture in Bosnia and HerzegovinA: Legal Overview (Kriminalističke teme, 2018)
Forfeiture of property obtained through the criminal act is an inescapable segment of modern legal systems and its answer to criminality. This is especially common in cases of organized and other serious forms of crime. Not only that forfeiture exercised one of the fundamental postulates of every criminal justice system that no one can keep property acquired by criminal offense but is the most effective way to fight organized crime which main purpose is to gain property benefits. Undoubtedly, therefore, without the adequate system of criminal property forfeiture there is no adequate mean to fight this type of crime. Article deals with legal provisions implemented in Bosnia and Herzegovina, when it comes to this institute of criminal justice. The subject of the analysis are the provisions of the substantive and procedural criminal laws, but also the lex specialis regulations related to this field and applied in Bosnia and Herzegovina at the entity and level of the Brčko District of Bosnia and Herzegovina. A special focus has been placed on the problems Bosnia and Herzegovina faces today in the implementation of this institute. These are the complexity of the legal system, issues related to interpretation of property forfeiture legal provisions and new forms of forfeiture that are not known to earlier jurisprudence such as extended confiscation of property gain.